Biodiesel Production From Bintanggur Oil (Callophyllum inophyllum L.) Using Calsium Oxide (CaO) Catalyst - Sutapa, I Wayan; Rosmawaty, Rosmawaty; Samual, Ismah (Indonesian Journal of Chemical Research, 2013)
The research of the biodiesel from bintanggur oil (Calophyllum inophyllum L.) using calsium oxide (CaO) catalyst had been done. In this study, a two-step process was used to produce biodiesel from bintanggur oil. Initially by esterification process using H2SO4 1.25% catalyst by weight of oil and methanol with a molar ratio of 1:9 and continued by transesterification process with 1:12 (oil : methanol) with the catalyst 8 wt% CaO. The esterification and the transesterification process carried out of 2 hours and 7 nespectively at a 65 °C. The synthesis of biodiesel was analyzed by FT-IR spectrophotometer. The conversion of biodiesel is 44.49%. The biodiesels properties were caracterized by ASTM method. Results of biodiesels properties there are specific gravity of 0.8878 g/cm3, viscosity kinematic 5.572 cSt, flash point 176.5 °C, pour point 9 °C, cooper strip corrosion 1b, and Conradson carbon residue 2.469%.